Knowledge and attitude on pre-menstrual syndrome among female college students of Kathmandu district. - Jha,Kaberi (2019)
ABSTRACT: Background: Premenstrual syndrome is used to describe physical, cognitive, affective, and behavioral symptoms that occur cyclically during the luteal phase of the menstrual cycle and resolve quickly at or within a few days of the onset of menstruation. Objective: The objective of this study was to identify the knowledge and attitude on pre menstrual syndrome and to identify the association between socio-demographic variable with the level of knowledge and attitude towards premenstrual syndrome among femalecollege students of Tarkeshwor MunicipalityKathmandu district. Methodology: A descriptive cross sectional study was conducted among the female students of higher secondary school aged 14-22 yearsof Tarkeshwor municipality. Self administered questionnaires were used for data collection. The questionnaires consisted of socio-demographic data, general information of respondent's menarche and menstruation, knowledge and attitude towards premenstrual syndrome. Results/Discussion:A total of 232 female respondents were involved in this study. Their age ranges from 14-22 years and mean age is 17.47 years. In this study, it is found that only 13.8% of the respondent had good knowledge on premenstrual syndrome, 65.1% of the respondent had average knowledge and had 21.1% of the respondent had poor knowledge regarding premenstrual syndrome. As 68.1% of the respondents had negative attitude towards premenstrual syndrome, 25% of them had ambivalent attitude towards premenstrual syndrome and only 6.9% of the respondent have positive attitude towards premenstrual syndrome.As previous study, conducted by Givshad RD (2016) in Iran found that only 3.6% of the respondent had good knowledge, 61.8% had average knowledge and 34.5% of them had poor knowledge. And according to previous study 9.1% respondent had negative attitude, 63.6% of them had ambivalent attitude and 27.3% had positive attitude towards premenstrual syndrome which shows that the level of knowledge is better than previous studies and attitude towards premenstrual syndrome is more negative in this study as compared to previous study. And there is no statistically significant between socio-demographic variable with level of knowledge and attitude towards PMS except father's occupation of the respondents. Conclusion:This research concludes that PMS is a common affecting the quality of life of women significantly. Despite the growing awareness, there remains a considerable deficiency of knowledge about the necessity to consult a doctor or seek any treatment for their symptoms and the attitude towards premenstrual syndrome is very poor.